Chemical Characterization of Coffee from Several Region of Indonesia (Cafein value, pH and Total Acid) - Ningrum, Sugiyati; Prayitno, Sutrisno Adi (Universitas Muhammadiyah Sidoarjo, 2023)
Coffee contains an active compound derived from the alkaloid group called caffeine. The content of active chemical compounds and various chemical properties of coffee are influenced by the area of the coffee is grown, the height of the plantation land, the type of coffee, and the processing process. In this research, a quantitative analysis of the chemical compounds and chemical properties of coffee from various regions in Indonesia was carried out with the aim of determining the caffeine content and acidity level (pH) as well as the total acid contained. This parameter is important to analyze due to it could influence the level of consumer acceptance. The method used in this research is the Completely Randomized Design (CRD) method using one research factor, the origin of the coffee area including Aceh coffee, Papua coffee, Wonosalam coffee, Sidikalang coffee and Ngawi coffee with the parameters observed being caffeine content, pH value and total titrated acid. The results showed that the caffeine content in Arabica Aceh, Excelsa Ngawi, Arabica Papua, Robusta Sidikalang and Excelsa Wonosalam meets the provisions of SNI 01-3542-2004, not more than 2% from 0.2% - 1.78%, the pH of these five coffee regions has significant differences from 5.69-6.55. These pH value has still considered safe for human consumption. Furthermore, the total acid value of these five types of coffee ranges from 0.97 to 1.36, with the total acid value of Sidikalang robusta being different from coffee from other regions.